Oxidative stress and inflammation: roles in osteoporosis - Luo, Jing; Li, Li; Shi, Wensen; Xu, Kangjie; Shen, Yucheng; Dai, Bin (Frontiers in Immunology, 2025)
Osteoporosis (OP) is a prevalent bone disease characterized by reduced bone mineral density (BMD) and compromised microstructure, leading to an increased risk of fractures and disability. With an aging global population, OP has become a significant public health issue, affecting over 200 million people worldwide. OP can be classified into primary (type I and type II) and secondary forms, with estrogen deficiency playing a critical role in postmenopausal OP. The pathophysiology of OP involves a complex interplay of factors, including cellular senescence, oxidative stress, inflammation, and hormonal imbalances. Bone homeostasis, maintained by the balance between osteoclast-mediated bone resorption and osteoblast-mediated bone formation, is regulated by various signaling pathways such as receptor activator of nuclear factor-κB ligand/receptor activator of nuclear factor-κB/osteoprotegerin (RANKL/RANK/OPG), interleukin-1/tumor necrosis factor-α (IL-1/TNF-α), and Notch. Disruption of these pathways, along with oxidative stress and chronic inflammation, leads to bone loss. Estrogen deficiency enhances pro-inflammatory cytokine production, increases osteoclast differentiation, and accelerates bone resorption. Furthermore, cellular senescence and oxidative stress contribute to reduced osteoblast function and increased adipogenesis in bone marrow mesenchymal stem cells (BMSCs). Chronic inflammation and oxidative stress further exacerbate the imbalance in bone remodeling, promoting osteoclast activity and impairing osteogenesis. Understanding the roles of immune dysregulation, oxidative stress, and inflammation in osteoporosis progression is crucial for developing targeted therapeutic strategies. This review discusses the molecular mechanisms underlying inflammation and oxidative stress in OP, highlights current therapeutic approaches, and proposes future research directions aimed at improving the prevention and treatment of osteoporosis.